Temperature and OH concentration measurements by ultraviolet broadband absorption of OH(X) in laminar methane/air premixed flames. (15th March 2021) - Yang, Xinyu; Peng, Zhimin; Ding, Yanjun; Du, Yanjun
Highlights: Gas temperature and OH mole fraction in CH4/air premixed flat flames were simultaneously measured by UV BAS. The measured results from BAS were compared with those from TDLAS and CFD, and good agreements were obtained. Compared with TDLAS, BAS has the distinct advantages of lower OH detection limits and higher temperature sensitivity. The advantages of BAS was analyzed theoretically and shown in experiments. Abstract: We report temperature and hydroxyl (OH) concentration measurements in methane/air premixed flat flames based on ultraviolet (UV) broadband absorption spectroscopy (BAS) of the OH electronic transitions ( X 2 Π - A 2 Σ + ). The temperature and OH mole fraction distributions were obtained at different heights above the burner for various equivalence ratios ( ϕ = 0.6, 0.7, 0.8, 0.93, and 1.06). The results agreed well with computational fluid dynamics (CFD) simulations using the AramcoMech 1.3 skeletal mechanism, which verifies the BAS measurement accuracy. For stable flames ( ϕ = 0.6, 0.7, and 0.8), the root-mean-square differences above the flat flames were all less than 16 K for the temperature and 150 ppm for the OH mole fraction. The BAS results also agreed with tunable diode laser absorption spectroscopy (TDLAS) measurements with a root-mean-square temperature difference of 31.5 K. Experimental and theoretical analysis demonstrates that the UV BAS OH detection limit is more than two orders of magnitude lower than that for infrared (IR) TDLAS, and the OH BAS temperature sensitivity is much higher than that for most line pairs in TDLAS measurements. These advantages make the UV BAS method an accurate method for combustion diagnostics, with more accurate temperature and OH concentration than IR TDLAS.